(untitled) (Romanian Studies Today, 2024)
This paper explores the transformative role of Romanian language education in the context of the recent influx of refugees into Romania. Focusing on the integration of Ukrainian refugees, the study delves into the necessity of adapting Romanian language education to meet the unique needs of this population. It underscores the pivotal role of culturally responsive teaching, trauma-informed pedagogies, and community engagement strategies in facilitating refugee integration. The analysis is segmented into key areas: defining the refugee experience, examining Romania’s response to the refugee crisis, and proposing innovative reforms in Romanian language teacher preparation programs. The paper advocates for the incorporation of multicultural education principles and a comprehensive, empathetic approach to language teaching. It highlights the potential long-term societal benefits of effectively integrating refugees through language education, including cultural enrichment and social cohesion. The study concludes by emphasizing the urgent need for educational reforms in Romania and suggests directions for future research to evaluate the impact of these changes.